2.17 RESTING-STATE FUNCTIONAL CONNECTIVITY BETWEEN THE SALIENCE AND DEFAULT MODE NETWORK AND ASSOCIATED COGNITIVE CONTROL IN ANOREXIA NERVOSA - Song, Inkyung; Cha, Jiook; Foerde, Karin; Attia, Evelyn; Steinglass, Joanna E.; Posner, Jonathan (Journal of the American Academy of Child and Adolescent Psychiatry, 2016)
Objectives: The neural correlates of impaired cognitive control in young adults/adolescents with AN remain poorly characterized. One candidate mechanism is altered intrinsic connectivity that coordinates internally versus externally directed processes, the default mode network (DMN) and salience network (SN), respectively. In this study, we examined the resting-state functional connectivity between the DMN and SN based on a cross-sectional and two longitudinal studies of AN. Methods: Across the three independent studies (n = 103), we defined the right anterior insula (AI) as a core node of the SN and examined its seedbased functional connectivity with the medial prefrontal cortex (MPFC; a core node within the DMN). Results: Relative to healthy control (HC) subjects, individuals with acutely ill AN in the cross-sectional study (n = 37) showed reduced inverse, or negative, connectivity between the SN and DMN (PFWE < 0.05). This finding was replicated in both longitudinal studies (n = 27 and 39; PFEW < 0.05). However, SN-DMN inverse connectivity in individuals with weight-restored AN increased to levels comparable with HC subjects (PFWE < 0.05). Exploratory analyses indicated that abnormal SN-DMN connectivity in underweight AN was associated with interference control (i.e., the Stroop test, PFWE < 0.05), but not with prepotent response inhibition (i.e., the continuous performance test). Conclusions: Reduced inverse connectivity between the SN and DMN, which may attenuate with treatment, may serve as a state biomarker of AN pathophysiology in relation to interference control essential for selective attention.